1, 3‐propanediol binds deep inside the channel to inhibit water permeation through aquaporins. (28th January 2016) - Yu, Lili; Rodriguez, Roberto A.; Chen, L. Laurie; Chen, Liao Y.; Perry, George; McHardy, Stanton F.; Yeh, Chih‐Ko
Abstract: Aquaporins and aquaglyceroporins (AQPs) are membrane channel proteins responsible for transport of water and for transport of glycerol in addition to water across the cell membrane, respectively. They are expressed throughout the human body and also in other forms of life. Inhibitors of human AQPs have been sought for therapeutic treatment for various medical conditions including hypertension, refractory edema, neurotoxic brain edema, and so forth. Conducting all‐atom molecular dynamics simulations, we computed the binding affinity of acetazolamide to human AQP4 that agrees closely with in vitro experiments. Using this validated computational method, we found that 1, 3‐propanediol (PDO) binds deep inside the AQP4 channel to inhibit that particular aquaporin efficaciously. Furthermore, we used the same method to compute the affinities of PDO binding to four other AQPs and one aquaglyceroporin whose atomic coordinates are available from the protein data bank (PDB). For bovine AQP1, human AQP2, AQP4, AQP5, and Plasmodium falciparum PfAQP whose structures were resolved with high resolution, we obtained definitive predictions on the PDO dissociation constant. For human AQP1 whose PDB coordinates are less accurate, we estimated the dissociation constant with a rather large error bar. Taking into account the fact that PDO is generally recognized as safe by the US FDA, we predict that PDO can be an effective diuretic which directly modulates water flow through the protein channels. It should be free from the serious side effects associated with other diuretics that change the hydro‐homeostasis indirectly by altering the osmotic gradients.